Study of forces during bipedal standing - Luengas, Lely A.; Gutierrez, Miguel A.; Camargo, Esperanza (Visión electrónica, 2014)
This study was designed to evaluate the average force under each foot and variation in location of center of plantar pressure during static standing, in amputees by landmines and non-amputees subjects. Fifteen subjects were evaluated (ten non-amputees, five men and five women, and five amputees, all men, age range 20-40 years), they are functional. Five measurements were performed for each subject, following the protocol established for the measurement. The template system Pedar was used. The statistical analysis used was ANOVA, to confirm that the data obtained in the measurements are valid. It was confirmed that the location of the COP on each foot is affected by the use of dentures, it is required to confirm whether the alignment of the prosthesis influences COP, is left for further study.